DETECTION FREQUENCY OF SEXUALLY TRANSMITTED INFECTION AGENTS IN CHRONIC CERVICITIS (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
In patients with social and anamnestic risk factors for the development of cervicitis, the vaginal microbiome should be assessed and a test performed for the presence of a possible causative agent of inflammation.